2000
DOI: 10.1038/sj.bjp.0703500
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin inhibits spontaneous and bradykinin‐induced but not oxytocin‐ or prostaglandin F‐induced periodic contraction of rat uterus

Abstract: In isolated rat uterine strips, adrenomedullin (AM) inhibited the spontaneous periodic contraction in a concentration-dependent manner (IC 50 =22.3+0.7 nM). The inhibitory eect of AM was prevented by either AM 22 ± 52 , a putative antagonist for AM receptors, or calcitonin gene-related peptide (CGRP) 8 ± 37 , a putative antagonist for CGRP receptors. AM also attenuated bradykinin (BK)-induced periodic uterine contraction, which was blocked by AM 22 ± 52 or CGRP 8 ± 37 , whereas AM had no eect on the periodic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 23 publications
3
20
1
Order By: Relevance
“…With regard to the reproductive system, ADM has been reported to generally act as a relaxant or vasodilator (Makino et al 1999, Yanagita et al 2000. However, the data presented in this paper show that locally expressed ADM can also function in the uterus in a more transient manner, since estrogen-induced ADM gene expression in the uterus only occurs in the stroma over a short period.…”
Section: Discussioncontrasting
confidence: 45%
“…With regard to the reproductive system, ADM has been reported to generally act as a relaxant or vasodilator (Makino et al 1999, Yanagita et al 2000. However, the data presented in this paper show that locally expressed ADM can also function in the uterus in a more transient manner, since estrogen-induced ADM gene expression in the uterus only occurs in the stroma over a short period.…”
Section: Discussioncontrasting
confidence: 45%
“…Studies in the rat have shown that AM inhibits uterine smooth muscle (spontaneous and bradykinin-induced) contraction [95] and that this effect may be mediated through an increase in cAMP [96]. However, Al-Ghafra et al [97] found significant increases in AM concentrations in the amnion and choriodecidua from women in labor compared with those from women not in labor, for both term and pre-term gestations.…”
Section: Preterm Deliverymentioning
confidence: 95%
“…This effect is prevented by antagonist of AM receptors or calcitonin gene-related peptide (CGRP) receptors. AM inhibits BK-induced periodic uterine contraction, but is unable to counteracts periodic contraction induced by OT or PGF2α, thus showing that AM is able to inhibit both spontaneous and BK-induced periodic contraction of uterus via activating receptors for AM and CGRP [24].…”
Section: Oxytocin (Ot)mentioning
confidence: 98%